Analisis Pengaruh Karakteristik Dewan Terhadap Manajemen Laba - Tang, Sukiantono; Shandy, Shandy (Gorontalo Accounting Journal, 2021)
This study aims to examine the effect of the characteristics of the board of directors on earnings management. Board characteristics are the most important part in the structure or governance of a company and government in limiting or preventing earnings management by a company manager. This study uses data from companies listed on the Indonesia Stock Exchange (IDX) which include annual reports from 2015 to 2019 except insurance companies, financial and banking institutions. Sampling of data was done by purposive sampling technique. This study combined the research object and one time dimension. This research was conducted using panel data regression test based on data that had been collected using SPSS and Eviews 10 software. The best model chosen for this research model was the Fixed Effect Model. The results showed that the board independent, board meeting, board of directors expertise, size of the audit committee, independent audit committee, audit committee meeting, audit committee expertise, leverage and big4 has no influence on the dependent variable earnings management. Then the size of the board of directors has a negative significant on earnings management. Meanwhile, company size and growth have a positive significant on earnings management.